Synthesis of A Novel PE-3030 Based WPUA Hybrid Binding Substance for Pigment Printing - Lahiri, Sudip Kumar; Kamruzzaman, Md; Talukder, Md Eman; Pervez, Md Nahid; Heng, Quan (Oriental journal of chemistry, 2017)
In this research, the waterborne polyurethane acrylate (WPUA) hybrid emulsions were first fabricated based on polyester polyol (PE-3030) and acrylic monomers via emulsion polymerization. The structures and thermal properties of prepared WPUAs were characterized by FT-IR and TGA. Then, physical properties of WPUAs i.e., average particle size, stability, viscosity; surface tension and solid content were determined. Some mechanical performances and solvent resistance of emulsions were also examined. Fabric screen printing application of the pigment-based inks formulated with the as-considered produced emulsion as a binder demonstrated good colour strength, fastnesses and handle of the printed fabrics compared to commercial binder. In addition, shows a significant improvement in tear strength and crease recovery angle properties. Particularly, PE-WPUA-10 sample was considered best due to exhibited superior performance in all properties. Synthesized polyester based WPUA is considered to be a future waterproof adhesive to fulfil the use standards for consumers.